The Development of Physics Teaching Materials Based On Local Wisdom To Improve Students’ Critical Thinking Ability - Landiana Etni Laos; Meti Tefu (STKIP Singkawang, 2020)
A research and development study had been conducted to evaluate the appropriateness of local wisdom based physics teaching material in order to increase students’ critical thinking skill. This study was based on 4-D development model including Define, Design, Develop, and Disseminate. Data was gathered from 30 research participantsin SMK Kristen Fautmolo. Observation, interview, questionnaire and test were data collection techniques. Before applying the instruments in data field, validation was garnered from 4 physics experts with 3.75 total score in very good category which indicated the developed material’s applicability in teaching and learning process. The result revealed that the local wisdom-based physics teaching material was effective to improve students’ critical thinking skill with 0.80 of N-gain score (high) and 89.91% of students’ responses toward learning using the material. Therefore, it could be concluded that the developed local wisdom-based physics material was appropriate to be used in physics learning and could improve student’s critical thinking skill.